EFEKTIFITAS METODE LOTUS BIRTH TERHADAP KEJADIAN ANEMIA DEFISIENSI ZAT BESI PADA BAYI - Parida Hanum; Sri Wahyuni Nasution (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2019)
The controversy over the Lotus Birth method for general application is still being debated, but the consensus to delay cord clamping and cutting has been agreed and agreed by WHO that the umbilical cord is clamped after stopping to beat to allow increased blood flow to the baby to prevent anemia. The objective of the research was to find effectiveness of the lotus birth method for the incidence of anemia in infants. The research is done by using quasy experiment with sample infants born spontaneously, having 38-40 weeks of pregnancy and without complications using the lotus birth method (15 people) and the control group not using the lotus birth method (15 people). Analysis method of data uses independent t-test. The result of the research showed no Effectiveness of the lotus birth method for the incidence of iron deficiency anemia in infants at the Klinik Pratama Sejahtera (p=0, 865). The conclusion in this study is no Effectiveness of the lotus birth method for the incidence of iron deficiency anemia in infants at the Klinik Pratama Sejahtera. It is expected that pregnant women should prepare themselves in the face of childbirth by increasing knowledge about how to maintain health and care for babies to avoid the occurrence of iron deficiency anemia.